Global Challenges for Innovation in Mining Industries - Daly, Alica; Humphreys, David; Raffo, Julio; Valacchi, Giulia (Social Sciences, 2022)
Offering the first in-depth global analysis of the innovation ecosystem in the mining industry, this book is aimed at policy-makers and academia alike. A wide range of international contributors assess this from different perspectives, using both a novel mining patent and innovation database and a wide set of analytical approaches.